Developing Mobile Clinical Decision Support for Nursing Home Staff Assessment of Urinary Tract Infection using Goal-Directed Design - Jones, Wallace; Drake, Cynthia; Mack, David; Reeder, Blaine; Trautner, Barbara; Wald, Heidi L (Applied Clinical Informatics, 2017)
Background: Unique characteristics of nursing homes (NHs) contribute to high rates of inappropriate antibiotic use for asymptomatic bacteriuria (ASB), a benign condition. A mobile clinical decision support system (CDSS) may support NH staff in differentiating urinary tract infections (UTI) from ASB and reducing antibiotic days.Objectives: We used Goal-Directed Design to: 1) Characterize information needs for UTI identification and management in NHs; 2) Develop UTI Decide, a mobile CDSS prototype informed by personas and scenarios of use constructed from Aim 1 findings; 3) Evaluate the UTI Decide prototype with NH staff.Methods: Focus groups were conducted with providers and nurses in NHs in Denver, Colorado (n = 24). Qualitative descriptive analysis was applied to focus group transcripts to identify information needs and themes related to mobile clinical decision support for UTI identification and management. Personas representing typical end users were developed; typical clinical context scenarios were constructed using information needs as goals. Usability testing was performed using cognitive walk-throughs and a think-aloud protocol.Results: Four information needs were identified including guidance regarding resident assessment; communication with providers; care planning; and urine culture interpretation. Design of a web-based application incorporating a published decision support algorithm for evidence-based UTI diagnoses proceeded with a focus on nursing information needs during resident assessment and communication with providers. Certified nursing assistant (CNA) and registered nurse (RN) personas were constructed in 4 context scenarios with associated key path scenarios. After field testing, a high fidelity prototype of UTI Decide was completed and evaluated by potential end users. Design recommendations and content recommendations were elicited.Conclusions: Goal-Directed Design informed the development of a mobile CDSS supporting participant-identified information needs for UTI assessment and communication in NHs. Future work will include iterative deployment and evaluation of UTI Decide in NHs to decrease inappropriate use of antibiotics for suspected UTI.Citation: Jones W, Drake C, Mack D, Reeder B, Trautner B, Wald HL. Developing mobile clinical decision support for nursing home staff assessment of urinary tract infection using goal-directed design.Appl Clin Inform 2017; 8: 632–650 https://doi.org/10.4338/ACI-2016-12-RA-0209
Keywords: Antimicrobial stewardship; urinary tract infections; clinical decision support; goal-directed design; nursing home; communications